Assessment of Effect of Comorbidities on Quality of Life of Pancreatitis Patients Using SF36V1 - Jessica, Nukabathini; Srujana, Danthala; Hasan, Mehedi; Azharuddin, Mohd; Chinnaeswaraiah, M. (Asian Journal of Biological and Life Sciences)
Introduction: Painful inflammation of the pancreas in the upper abdomen is a common risk factor for acute pancreatitis, affecting individuals of all ages, especially newborns. Risk factors include alcohol consumption, gallstones, obesity, and dietary habits. Materials and Methods: The cross-sectional observational study was conducted for 6 months and the effect of complications in Acute Pancreatitis Patients was assessed by using SF-36 V1 scale. Results: A cross-sectional observational study in Khammam found that alcoholic pancreatitis patients experience functional impairment due to factors like dietary habits and cholelithiasis. The incidence of acute pancreatitis increased due to obesity and gallstones. Conclusion: According to our study the pancreatitis patients experienced more impairment of their Physical and social functioning in order to improve the health they should avoid social habits and improve the quality of life.
Keywords: Acute Pancreatitis; Alcohol consumption; Pathophysiology; Comorbidities; SF36V1; Quality of life.